Parishin C's prevention of Aβ1-42-induced inhibition of long-term potentiation is related to NMDA receptors - Zhihui Liu; Weiping Wang; Nan Feng; Ling Wang; Jiangong Shi; Xiaoliang Wang (Elsevier, 2016)
The rhizome of Gastrodia elata (GE), a herb medicine, has been used for treatment of neuronal disorders in Eastern Asia for hundreds of years. Parishin C is a major ingredient of GE. In this study, the i.c.v. injection of soluble Aβ1-42 oligomers model of LTP injury was used. We investigated the effects of parishin C on the improvement of LTP in soluble Aβ1-42 oligomer-injected rats and the underlying electrophysiological mechanisms. Parishin C (i.p. or i.c.v.) significantly ameliorated LTP impairment induced by i.c.v. injection of soluble Aβ1-42 oligomers. In cultured hippocampal neurons, soluble Aβ1-42 oligomers significantly inhibited NMDAR currents while not affecting AMPAR currents and voltage-dependent currents. Pretreatment with parishin C protected NMDA receptor currents from the damage induced by Aβ. In summary, parishin C improved LTP deficits induced by soluble Aβ1-42 oligomers. The protection by parishin C against Aβ-induced LTP damage might be related to NMDA receptors.